Language of Eating Practices in the Population: A Communication on the Need to Culturally Adapt Dietetic Guidelines - Laguna-Camacho, Antonio (CV. Global Health Science Group, 2021)
The present paper underlines the relevance of identifying the terms used by members of the public to describe their eating practices. This is illustrated reviewing a series of studies in which examples of prevalent eating practices were self-reported by individuals. The argument is made that there are clear distinctions identified by the language manifested by individuals about different types of eating behaviour. The need is addressed to consider terminology elicited from members of a culture about their eating behaviour in the formulation of dietetic recommendations in order to incorporate the cultural context and enhance the specificity of widespread eating practices that can be carried out to reduce chronic diseases.